STUDI KOMPARATIF HASIL BELAJAR MELALUI MODEL PEMBELAJARAN PROBLEM SOLVING DAN PROBLEM POSING - Ida Nuri Fitria; Eddy Purnomo; Erlina Rupaidah (JEE (Jurnal Edukasi Ekobis), 2013)
This research  know comparison study economics  learning problem solving model students using  learning problem posing model. The methods  used experiment and comparative research. The study design used treatment by level,cluster random sampling. collect data  used observation, interview, questionnaire , study post test. The test   hypothesis uses Anava and T-test varian two ways. Based the results research: (1) there differences average  studied economics among students  using Problem Solving learning and Problem Posing model (2) average results studied economics students  study using  learning Problem Solving model higher than  study using  learning model Posing Problems  students  have  positive attitude towards subject. (3) average results studied economics students study using  learning Problem Solving model lower than  study using learning Problem Posing  students have  negative attitude towards the subject . (4) there is no interaction between  learning model and attitude   students towards  economic subjects. Penelitian ini bertujuan mengetahui perbandingan hasil belajar Ekonomi yang menggunakan model pembelajaran problem solving  dengan  pembelajaran problem posing. metode penelitian eksperimen dengan pendekatan komparatif . Desain penelitian treatment by level Teknik sampling cluster random sampling. Teknik pengumpulan data  observasi, wawancara, angket tes hasil belajar. Pengujian hipotesis menggunakan rumus analisis varians dua jalan dan t-test dua sampel independen. Berdasarkan analisis data diperoleh: (1) terdapat perbedaan rata-rata hasil belajar antara siswa yang pembelajaranya menggunakan model pembelajaran Problem Solving dan model pembelajaran Problem Posing. (2) rata-rata hasil belajar yang pembelajaranya menggunakan model pembelajaran Problem Solving lebih tinggi dibandingkan menggunakan model pembelajaran Problem Posing bagi siswa yang memiliki sikap positif terhadap mata pelajaran (3) rata-rata hasil belajar  pembelajaranya menggunakan model pembelajaran Problem Solving lebih tinggi dibandingkan yang pembelajaranya menggunakan model pembelajaran Problem Posing bagi siswa yang memiliki sikap negatif terhadap mata pelajaran.(4) tidak ada interaksi antara model pembelajaran dan sikap siswa terhadap mata pelajaran. Kata kunci: hasil, ps, pp, sikap